2017
DOI: 10.3389/fmicb.2017.01022
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Signaling in Intestinal Mucosa Epithelium Suggests the Existence of an Active Inter-kingdom Crosstalk Mediated by Exosomes

Abstract: The human intestinal mucosal surface represents the first defense against pathogens and regulates the immune response through the combination of epithelial cell (EC) functions and immunological factors. ECs act as sensors of luminal stimuli and interact with the immune cells through signal–transduction pathways, thus representing the first barrier that HIV-1 virus encounters during infection. In particular, the HIV-1 Nef protein plays a crucial role in viral invasion and replication. Nef is expressed early dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…EVs may also modulate retroviral pathogenesis [ 86 , 87 ]; HIV and simian immunodeficiency viruses modulate vesicle secretion through the Nef protein, which is secreted in exosomes and modifies intracellular trafficking pathways, enhancing viral infectivity and regulating host gene expression and immune responses [ 88 , 89 , 90 , 91 ]. In addition, TNFα release by cells upon incorporation of exosomes secreted by infected cells may reactivate latent HIV-1 [ 92 ].…”
Section: Evs In Viral Infectionsmentioning
confidence: 99%
“…EVs may also modulate retroviral pathogenesis [ 86 , 87 ]; HIV and simian immunodeficiency viruses modulate vesicle secretion through the Nef protein, which is secreted in exosomes and modifies intracellular trafficking pathways, enhancing viral infectivity and regulating host gene expression and immune responses [ 88 , 89 , 90 , 91 ]. In addition, TNFα release by cells upon incorporation of exosomes secreted by infected cells may reactivate latent HIV-1 [ 92 ].…”
Section: Evs In Viral Infectionsmentioning
confidence: 99%
“…The authors further showed that this disruption was due at least in part to a Nef-induced downregulation of zona occludin-1, also referred to as tight junction protein 1, which they hypothesized weakened the tight junctions between endothelial cells [107]. The effects of secreted Nef, exosomal and otherwise, on tight junction integrity has led to speculation that exosomes containing Nef may contribute to endothelial disruption in the gut as well, though there is not much evidentiary support for that hypothesis as of yet [108]. It is also of note that other HIV proteins such as Tat, Vpr, and gp120 also weaken the BBB by several mechanisms, such as downregulation and/or oxidative stress-induced phosphorylative dysregulation of tight junction proteins [109].…”
Section: Consequences Of Exosomal Delivery Of Hiv Elementsmentioning
confidence: 99%
“…Also, bacteria can sense various components of the immune system such as cytokines, apolipoprotein B (ApoB), Nox2, and antimicrobial peptides, modulating the host immune responses [92]. The possibility of interkingdom communication between Nef protein of HIV-1 virus and the host through exosomes has been recently reviewed, which extends the existence of QS other than in bacteria [94]. Likewise, QS can occur in animals and plants [92].…”
Section: Communication Between Bacteria and Hostsmentioning
confidence: 99%